Teori Efek Jera dalam Penerapan Sanksi Qanun Jinayat terhadap Jarimah Perzinahan di Nanggroe Aceh Darussalam Perspektif Hukum Pidana Islam - Deryasa; Alfi Munawar Djoharuddin; Alfin Kamaludin; Afif Ilyas Zaqlul; Deden Najmudin (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The application of qanun jinayat is still under discussion among academics, including the punishment of flogging for adultery and liwath as stipulated in Qanun Aceh Number 6 of 2014 concerning Jinayat Law. The theory of deterrence in Islamic criminal law also provides a purpose for punishment to prevent (al-Zajr) and educate (al-Tahdib), which raises academic questions about the appropriateness of applying Aceh's qanun jinayat to the jarimah of adultery. The purpose of this study is to conduct a normative review of the legal provisions governing the imposition of penalties for adultery in the Aceh Jinayah Qanun, particularly for the crimes of adultery and liwath, and to analyze the effectiveness of the application of these penalties in order to provide insights related to the theory of deterrence in the application of these penalties. The research method used is qualitative with a normative juridical approach sourced from primary data such as the Qur'an, hadith, regulations, and secondary data as supporting evidence. The results of the study show that there is a slight imbalance between the purpose of punishment (deterrent effect) and its application, so it is recommended to reconstruct it by harmonizing it with future regulations. Therefore, this study can contribute to Islamic legal scholarship and serve as material for the government to evaluate in formulating other regulations.